2021
DOI: 10.1021/acsapm.1c00297
|View full text |Cite
|
Sign up to set email alerts
|

(Bis)phosphonic Acid-Functionalized Poly(ethyleneimine)–Poly(amido amine)s for Selective In Vitro Transfection of Osteosarcoma Cells

Abstract: Osteosarcoma is aggressive bone cancer, whose treatment has not changed significantly for the past few decades. Although gene therapy methods have emerged as potential treatment routes, the need for efficient and nontoxic gene delivery systems targeting osteosarcoma cells remains a challenge. Highmolecular-weight poly(ethyleneimine)s (PEIs) are used as universal transfection agents; however, they cause significant cytotoxicity. On the other hand, poly(amido amine)s (PAAs) are biocompatible, biodegradable polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In this context, a good tropism of CNCs and (bis)phosphonate-CNC conjugates for bone tissues 7,9 makes them great candidates for the treatment of bone metastasis and osteosarcoma. 9,10 Additionally, we demonstrated that the delivery of ApA via CNCs also potentiates beneficial immunomodulatory effects of ApA up to 5 times, as compared to the soluble form of ApA. These results suggest that, in potential clinical application, a smaller amount of bisphosphonates would be required if they are delivered via CNC, which is especially important when adverse clinical effects of these drugs are considered.…”
Section: Dovepressmentioning
confidence: 65%
See 1 more Smart Citation
“…In this context, a good tropism of CNCs and (bis)phosphonate-CNC conjugates for bone tissues 7,9 makes them great candidates for the treatment of bone metastasis and osteosarcoma. 9,10 Additionally, we demonstrated that the delivery of ApA via CNCs also potentiates beneficial immunomodulatory effects of ApA up to 5 times, as compared to the soluble form of ApA. These results suggest that, in potential clinical application, a smaller amount of bisphosphonates would be required if they are delivered via CNC, which is especially important when adverse clinical effects of these drugs are considered.…”
Section: Dovepressmentioning
confidence: 65%
“… 8 In line with this, the delivery of anti-osteoporotic phosphonates and cytotoxic drugs via CNCs has been considered an attractive approach for the therapy of osteosarcoma and bone metastasis. 9 , 10 Namely, phosphonates, such as alendronate (ALN) and 3-aminopropyl phosphonic acid (ApA), were shown to inhibit osteoclast-mediated bone resorption and increase bone mineralisation. 11 , 12 Moreover, we showed previously that ALN and ApA conjugated to CNCs display good biocompatibility and the growth of primary human osteoblasts, 13 all of which could be desirable in treating bone diseases with prominent osteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives of PEI have been extensively studied as antimicrobial agents, , as nonviral transfection vectors, , and for other biomedical applications. , The results, however, have shown that the polymer exhibits relatively high cytotoxicity, which limits its applications to nonmedical uses such as antibacterial coatings or paints. , On the other hand, polytrimethylenimine (PTMI), an analogue of PEI with a three-methylene spacer between amine groups, has received substantially lower attention. Its dendrimeric form has gained popularity as a nonviral transfection vector and in drug delivery systems, , although there are very limited reports on a linear form of PTMI. Different N -methylated PTMI derivatives were synthesized; ,, however, they have not been the subject of antimicrobial studies.…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies also show that they are able to improve bacterial susceptibility for β-lactam antibiotics. 15 Derivatives of PEI have been extensively studied as antimicrobial agents, 16,17 as nonviral transfection vectors, 18,19 and for other biomedical applications. 19,20 The results, however, have shown that the polymer exhibits relatively high cytotoxicity, which limits its applications to nonmedical uses such as antibacterial coatings or paints.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation